Positive Affect and Inflammatory Activity in Breast Cancer Survivors: Examining the Role of Affective Arousal. Issue 5 (June 2016) - Moreno, Patricia I.; Moskowitz, Andrew L.; Ganz, Patricia A.; Bower, Julienne E.
ABSTRACT: Objective: Given the importance of positive affect and inflammation for well-being in cancer survivors, the current study examined the relationship between high- and low-arousal positive affect and inflammation in 186 women who completed treatment of early-stage breast cancer. Methods: Measures of high- and low-arousal positive affect were completed within 3 months after treatment completion (baseline). Plasma markers of inflammation, including soluble tumor necrosis factor receptor type II (sTNF-RII), C-reactive protein (CRP), and interleukin-1 receptor antagonist, were assessed at baseline and 6- and 12-month follow-up assessments. Results: Multilevel modeling analyses showed that high-arousal positive affect was associated with lower levels of sTNF-RII, a marker of TNF activity, at treatment completion and prospectively predicted maintenance of these differences through the 6- and 12-month follow-ups adjusting for biobehavioral confounds ( b = −0.055, t (156) = −2.40, p = .018). However, this association was no longer significant when adjusting for fatigue. Exploratory analyses showed that low-arousal positive affect was associated with lower levels of CRP at treatment completion and through the 6- and 12-month follow-ups; this association remained significant after adjusting for fatigue and other confounds ( b = −0.217, t (152) = −2.04, p = .043). Conclusions: The relationship of high-arousal positive affect (e.g., "active") with sTNF-RII seems to be driven by the overlap of high-arousal positive affect with fatigue, whereas the relationship of low-arousal positive affect (e.g., "calm") with CRP was independent of fatigue. Future research should consider affective arousal when examining the association of positive affect with inflammation as this facet of positive affect may have important implications for interpretation of results.